Advanced X-ray Imaging Technology - Pfeiffer, Daniela; Pfeiffer, Franz; Rummeny, Ernst (Springer, 2020)
Since their discovery by Wilhelm Conrad Röntgen in 1895, X-rays have become the most widely available, typically fastest, and usually most cost-effective medical imaging modality today. From the early radiographic approaches using X-ray films as detectors, the portfolio of medical X-ray imaging devices developed into a large range of dedicated instrumentation for various applications. While X-ray imaging has come a long way, there are some physical properties of X-rays, which have not yet been fully exploited, and which may offer quite some room for further enhancements of current X-ray imaging equipment. Firstly, X-ray imaging today is mainly black and white, despite the fact that X-ray generators actually create a full spectrum of X-ray energies, and that the interactions of X-rays that occur within the human body are not the same for all energies and every material. Exploiting these spectral dependencies allows to not only obtain a black and white CT image, but also to obtain more molecularly specific information, which is relevant particularly in oncological precision radiology. The second aspect of X-rays, and so far in radiology mainly neglected and unused, is the physical fact that X-rays can also be interpreted in the wave picture, and not only as presently been done in the particle picture. If interpreted as waves, X-rays—just like visible light—experience a phase shift in matter, and this—if exploited correctly—can produce a new class of X-ray images, which then depict the wave interactions of X-rays with matter, rather than only the attenuating properties, as done until now.
CRIS-Team Scopus Importer:2023-03-08